Refractive, corneal and ocular residual astigmatism: distribution in a German population and age-dependency - the Gutenberg health study - Schuster, Alexander K.; Mirshahi, Alireza (Graefe's archive for clinical and experimental ophthalmology, 2017)
PurposeWorldwide, the most frequent cause of visual impairment is uncorrected refractive error. This analysis focused on the distribution and associations of refractive, corneal and ocular residual astigmatism.MethodsAs part of the Gutenberg Health study, a population-based cross-sectional study was conducted in the general population of Germany. A comprehensive ophthalmological examination including refraction, tonometry, and Scheimpflug imaging of the anterior cornea (Pachycam) was performed. In addition to the magnitude and type (with-the-rule, against-the-rule, oblique) of the refractive or corneal astigmatism, we calculated the vector components (J0, J45) of both astigmatisms and calculated the ocular residual astigmatism. We performed multiple quantile regression analysis to evaluate the factors associated with refractive, corneal and ocular residual astigmatisms.ResultsA total of 13,558 subjects (49% female) with a mean age of 54.0 years (range 35-74 years) were included in this study. The prevalence of refractive astigmatism (>1.0D) was 13.0% in right eyes and 12.0% in left eyes, and 85% of these subjects wore spectacles. The distribution of refractive astigmatism showed a two-peak distribution with high astigmatism for with-the-rule and against-the-rule astigmatism. The associated factors were corneal curvature, age and sex for the different astigmatisms (p < 0.001).ConclusionsWe analyzed the prevalence of different astigmatisms within a European population. We confirmed a shift with aging from with-the-rule to against-the-rule astigmatism to refractive and corneal astigmatism. Astigmatism has a large impact on visual perception; more than 85% of people with astigmatism over one diopter wore glasses for distance vision.
Gesehen am 10.10.2018